Atorvastatin attenuates obese-induced kidney injury and impaired renal organic anion transporter 3 function through inhibition of oxidative stress and inflammation - Nattavadee Pengrattanachot (2020)
© 2020 Elsevier B.V. An excessive consumption of high-fat diet can lead to the alterations of glucose and lipid metabolism, impaired insulin signaling and increased ectopic lipid accumulation resulting in renal lipotoxicity and subsequent renal dysfunction. Atorvastatin is a lipid-lowering drug in clinical treatment. Several studies have reported that atorvastatin has several significant pleiotropic effects including anti-inflammatory, antioxidant, and anti-apoptotic effects. However, the effects of atorvastatin on metabolic disturbance and renal lipotoxicity in obesity are not fully understood. In this study, obesity in rat was developed by high-fat diet (HFD) feeding for 16 weeks. After that, the HFD-fed rats were received either a vehicle (HF), atorvastatin (HFA) or vildagliptin (HFVIL), by oral gavage for 4 weeks. We found that HF rats showed insulin resistance, visceral fat expansion and renal lipid accumulation. Impaired renal function and renal organic anion transporter 3 (Oat3) function and expression were also observed in HF rats. The marked increases in MDA level, renal injury and NF-κB, TGF-β, NOX-4, PKC-α expression were demonstrated in HF rats. Atorvastatin or vildagliptin treatment attenuated insulin resistance and renal lipid accumulation-induced lipotoxicity in HFA and HFVIL rats. Moreover, the proteins involved in renal inflammation, fibrosis, oxidative stress and apoptosis were attenuated leading to improved renal Oat3 function and renal function in the treated groups. Interestingly, atorvastatin showed higher efficacy than vildagliptin in improving insulin resistance, renal lipid accumulation and in exerting renoprotective effects in obesity-induced renal injury and impaired renal Oat3 function.